Meningkatkan Keterampilan Roll Depan pada Pembelajaran Senam Lantai Peserta Didik Kelas VII G SMP Negeri 7 Kediri Menggunakan Pendekatan Bermain: Penelitian - Adji Prakasa Azis; Septiyaning Lusianti; Muhammad Rofi’Ussya’en (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Physical education, sports, and health (PE) is an integral part of the education curriculum that aims to develop motor skills, fitness, and sportsmanship values. One of the materials in PJOK is floor gymnastics, where the forward roll (forward roll) is the basis for mastering other gymnastic movements. This study aims to improve forward roll skills in floor gymnastics learning for class VII G students of SMP Negeri 7 Kediri using a play approach. This study uses a Classroom Action Research (CAR) approach that utilizes the Kemmis and McTaggart model for its design. The findings state that there is an increase in the average value and percentage of student compliance in cycle II when compared to cycle I. Therefore, the study was concluded in cycle II because the objectives set by the school have been achieved.